HUMAN RESOURCE MANAGEMENT THROUGH ROTATION, MUTATION AND MOTIVATION IN EMPLOYEE JOB SATISFACTION SEMBUNG BATIK KULON PROGO - Marwanti, Retno Deni; Subiyanto, Didik; Kusuma, Nala Tri (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to examine Human Resource Management through Rotation, Transfer and Motivation in the Job Satisfaction of Sembung Batik Kulon Progo Employees. The type of research used in this research is quantitative descriptive research. The sampling technique used was saturated sampling. The sample of respondents in this research were Sembung Batik employees. The test results show that rotation has a positive effect on job satisfaction, mutation has a positive effect on job satisfaction, motivation has a positive effect on job satisfaction. The results of this research indicate that employees need to be given training because training is a learning process for employees to carry out their work as well as possible. Leaders must also be consistent in maintaining and increasing job satisfaction so that employees are motivated to work.